No role for the Hartz reforms? Demand and supply factors in the German labor market, 1993-2014 - Michael C. Burda; Stefanie Seele (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
The supply and demand framework of Katz and Murphy (1992) provides new evidence on the source of changes in socially insured full-time and part-time employment in years preceding and following the implementation of the landmark Hartz reforms in Germany. Our findings are consistent with a stable demand for labor, especially in western Germany, implying that supply factors were decisive for the evolution of the labor market after 2003. The correlation of changes in wages and labor force participation is also consistent with a positive labor supply shock at a given working-age population. We also show that part-time employment played a decisive role in the post-2003 improvement of the German labor market.
Keywords: E24; J21; 330; German labor market miracle; Hartz reforms; part-time work; wage inequality